2015
DOI: 10.1016/j.pmrj.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Lumbar Stability During Wall Plank‐and‐Roll Activity Using Inertial Sensors

Abstract: Certain amounts and patterns of lumbar postural changes were observed in healthy young subjects, with no significant variations based on gender, rolling side, or truncal muscle power. Application of the evaluation on LBP patients revealed prominent deviations from the healthy postural changes, suggesting potential clinical applicability. Therefore, with appropriate development and case stratification, we believe that the quantification of lumbar postural changes during WPR activity can be used to assess dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Specifically, LBP patients had higher lateral bending maximum angle and higher lateral bending excursion, but similar lateral bending static angle (a demonstration of this motor pattern is available on Supplementary Video 1). This finding is in agreement with the observations reported by Yoon et al, who found that all 3 patients with LBP had greater lateral bending excursion than the average noted in healthy participants .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Specifically, LBP patients had higher lateral bending maximum angle and higher lateral bending excursion, but similar lateral bending static angle (a demonstration of this motor pattern is available on Supplementary Video 1). This finding is in agreement with the observations reported by Yoon et al, who found that all 3 patients with LBP had greater lateral bending excursion than the average noted in healthy participants .…”
Section: Discussionsupporting
confidence: 94%
“…One of the main goals of the present study was to determine whether the patterns observed in Yoon et al's study could be replicated in a larger sample. In agreement with those results, we have found that gender does not affect the lumbar motion patterns in healthy individuals during the WPR test.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations